Philippine eSports Training Center for extended reality technologies - Presbitero, Aldritz F.; Madrid, Dolores Cecilia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Esports has taken the spotlight as one of the growing industries in recent times. eSports
being sedentary in nature, has been associated with several health risks. eSports
athletes experience physical and mental health issues due to the training conditions and
lack of purpose-built facilities that will accommodate their unique needs. The green
mind theory (GMT) suggests that having a green mind produces positive behaviors that
shape the environment. GMT comprises 4 key principles: Place-making, Habits into
routine, Immersion to interactive activities, Natural and social engagement. These
components are the strategies to achieve a ‘green mind’. The emergence of extended
reality (XR) technologies creates an innovative approach in promoting physical activity
for eSports athletes. Virtual reality (VR) exergames immerse eSports athletes into a
new variety of physical and mental training in improving their eSports performance.
Incorporating both concepts, the designer reshapes and reimagines a new eSports
training facility that will promote health and well-being for eSports athletes. Taking
into account the influence of COVID-19 pandemic, it is significant to realize the
changes of our social behaviors that affect our physical environment. Adjustments to
the ‘new normal’ through transition spaces are necessary in reconnecting eSports
athletes with the ‘outside world’
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: eSports; Training facilities